A Two-Stage Adaptive Laboratory Evolution Strategy to Enhance Docosahexaenoic Acid Synthesis in Oleaginous Thraustochytrid - Wang, Sen; Wan, Weijian; Wang, Zhuojun; Zhang, Huidan; Liu, Huan; Arunakumara, K. K. I. U.; Cui, Qiu; Song, Xiaojin (Frontiers in Nutrition, 2021)
Thraustochytrid is a promising algal oil resource with the potential to meet the demand for docosahexaenoic acid (DHA). However, oils with high DHA content produced by genetic modified thraustochytrids are not accepted by the food and pharmaceutical industries in many countries. Therefore, in order to obtain non-transgenic strains with high DHA content, a two-stage adaptive laboratory evolution (ALE) strategy was applied to the thraustochytrid Aurantiochytrium sp. Heavy-ion irradiation technique was first used before the ALE to increase the genetic diversity of strains, and then two-step ALE: low temperature based ALE and ACCase inhibitor quizalofop-p-ethyl based ALE were employed in enhancing the DHA production. Using this strategy, the end-point strain E-81 with a DHA content 51% higher than that of the parental strain was obtained. The performance of E-81 strain was further analyzed by component analysis and quantitative real-time PCR. The results showed that the enhanced in lipid content was due to the up-regulated expression of key enzymes in lipid accumulation, while the increase in DHA content was due to the increased transcriptional levels of polyunsaturated fatty acid synthase. This study demonstrated a non-genetic approach to enhance lipid and DHA content in non-model industrial oleaginous strains.